Multi-local Arrangements and Impact on Work-Life Balance. An International Research on Flight Attendants - Tremblay, Diane-Gabrielle; Gillet, Anne (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2024)
Multi-locality and mobility issues have recently appeared as an important research subject. Flight attendants and civil aviation personnel are clearly amongst the main professional groups concerned with this issue of multi-locality. In our research, we analyzed the impacts of this situation and mobility on work-life balance, comparing the situation in Canada, Germany and France. Our research is based on an online survey and also on interviews conducted with cabin crews in these three countries. The research shows that the challenges in multi-locality, and multiple layovers in the specific case of cabin crews, lead to many issues as concerns workloads, working time and work-life balance, themes that are central to our research and will be discussed in this article. While the majority of flight attendants agreed that layovers are opportunities to spend time with colleagues, the fatigue levels and shortness of layovers at destination combined with the number of legs can imply that respondents are often not in the mood to socialize with the crew and mainly focus on recovering for the next flight. Regarding work-life balance, work demands were more likely to interfere with family life than the contrary. Many reported that the requirements of their work in terms of mobility and working time interfered with their home and family life, and this was put forward in the survey as in the interviews we conducted. The unpredictability of the schedule in the first years of one’s career brings along a lot of child care issues for parents. Even though the flight attendants’ schedule is flexible per se, only a minority of respondents reported having a flexible schedule (7% of French; 16% of German and 40% of Canadian respondents), indicating that the flexibility is rather employer-driven than employee-driven, which has clearly different impacts. With the mobility and multi-locality issue, which is characteristic of the flight attendants’ work, this represents an important challenge for cabin crew.